Penerapan Sistem Antrian Sebagai Upaya Mengoptimalkan Pelayanan Rekonsiliasi Barang Milik Negara (BMN) Di Kantor Pelayanan Kekayaan Negara Dan Lelang Palu - Resnawati; Delfianti, D; Jaya, A I (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2020)
ABSTRACT The queue is an activity that arises because of the number of services the facility is less than the number who need the service. Kantor Pelayanan Kekayaan Negara dan lelang(KPKNL) Palu is one of the government agencies that implement a queuing system on reconciliation of State Owned Property (BMN) that it held every semester, where they just served the 337 of work units comparethe 700 of work unit within two weeks. This study aimed is to obtain the characteristics of the queue and the optimum number of servers in the service of reconciliation in KPKNL Palu using queues. The results showed the busiest time is on July 21, 2016. The addition of a server from 4 to 8 servers showed a decrease in the queue. It is perceptibly from a queue characteristics decrease in levels of activity server (Ï) from 75% to 20,8%, the number of work units waiting in the queue (Lq) of 1,53 2work units/ hour to 0 work unit/hour, the number of work units waiting in the system (Ls) of 4,53 5 work units/hour into 1,667 2 work units/hour, time waiting in queues (Wq) of 6,11 minutes to 0 minutes, the waiting time in the system ( Ws) of 18,11 minutes to 6,667 minutes and the number of work units that is served in 2 weeks are 700 work units. Keywords : Characteristics, Queue, Reconciliation of State Owned Property (BMN).